1999
DOI: 10.3758/bf03209977
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of fear to an extinguished conditioned context

Abstract: Rats were shocked in the black but not the white compartment of a shuttlebox and then exposed to the black compartment in the absence of the shock unconditioned stimulus (US) to extinguish fear responses (passive avoidance). In five experiments, rats were then shocked in a reinstatement context (distinctively different from the shuttlebox) to determine the conditions that reinstate extinguished fear responding to the black compartment. Rats shocked immediately upon exposure to the reinstatement chamber failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The results of these studies are not always consistent. For example, while Bouton and Bolles (1979) claimed that reinstatement could only be found when after extinction the USs were presented in the test context, Richardson, Duffield, Bailey and Westbrook (1999) observed reinstatement in a test context different from the reinstatement context.…”
Section: Introductionmentioning
confidence: 95%
“…The results of these studies are not always consistent. For example, while Bouton and Bolles (1979) claimed that reinstatement could only be found when after extinction the USs were presented in the test context, Richardson, Duffield, Bailey and Westbrook (1999) observed reinstatement in a test context different from the reinstatement context.…”
Section: Introductionmentioning
confidence: 95%
“…This reduction only occurs in the context where extinction training takes place; in other contexts, there is are-emergence of the fear response, known as contextual renewal (Bouton, 2004;Bouton, Westbrook, Corcoran, & Maren, 2006;Rauhut, Thomas, & Ayres, 2001). The reemergence of the CR following extinction has also been observed under other situations, such as spontaneous recovery and reinstatement (Bouton & Bolles, 1979;Haberlandt, Hamsher, & Kennedy, 1978;Harris, Jones, Bailey, & Westbrook, 2000;Pavlov, 1927;Quirk, 2002;Rauhut et al, 2001;Rescorla & Heth, 1975;Richardson, Duffield, Bailey, & Westbrook, 1999;Robbins, 1990;Schiller et al, 2008), supporting the idea that the original fear memory is preserved and that extinction represents the formation of a new inhibitory association rather than erasure of the original memory (Bouton et al, 2006;Haberlandt et al, 1978;Quirk, 2002;Robbins, 1990;Schiller et al, 2008). Since the expression of renewal appears to depend on several factors (Cahill & Milton, 2019;Chen, Wang, Wang, & Li, 2017;Goode & Maren, 2014), understanding how the re-emergence of fear could be controlled is of fundamental importance for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent studies have demonstrated that timing of reinstatement US presentation with respect to reinstatement context onset has an impact on the degree of reinstatement (Richardson et al 1999), an experimental detail which has not been given attention in human work. Furthermore, experimental phases (acquisition, extinction, reinstatement, reinstatement test) usually take place on distinct days while in human studies they often follow upon each other immediately (see Table 2), which hampers translation between species.…”
Section: Experimental Timingmentioning
confidence: 99%